Design methodology and thermal modelling of industrial scale reactor for solid state hydrogen storage. (26th July 2019) - Raju, Nithin N.; Muthukumar, P.; Selvan, P. Vivek; Malleswararao, K.
Abstract: In this study, a novel set of comprehensive arithmetic correlations has been proposed to design an industrial scale cylindrical reactor with embedded cooling tubes (ECT) for metal hydride (MH) based hydrogen storage and thermal management applications. Based on ASME standards, different nominal pipe sizes were imparted into a cylindrical reactor design with ECT to accommodate 50 kg of LaNi4.7 Al0.3 alloy. A three dimensional numerical model has been developed using COMSOL Multiphysics 4.3a to predict the hydriding performance of designed reactors, which was further experimentally validated as well. At an absorption condition of 30 bar supply pressure and 298 K absorption temperature with 60 lpm volumetric HTF flow rate, 6 inch reactor with 99 ECT portrayed better heat transfer characteristics. From the parametric investigation, it is observed that the variation of supply pressure has predominant effect followed by the variation of the HTF flow rate on hydriding (absorption) kinetics of the device. However, the variation of absorption temperature has minuscule influence on the hydriding performance. At a supply condition of 30 bar and 298 K with water flow rate of 30 lpm, a hydrogen storage capacity (HSC) of 1.29 wt% was achieved within 2060 s. Highlights: A comprehensive design methodology for industrial scale MH reactor is proposed. Analysed different reactor configurations to decide the best suitable model. Numerical predictions are validated with experimental data. Parametric studies on reactor filled with 50 kg MH is carried out. Optimum operating range of LaNi4.7 Al0.3 based industrial scale system is predicted.